PROTECTION OF ARABIC LANGUAGE IN RELATION WITH INFLUX FROM ENGLISH TAKING OVER WITH SHOPS TITLE AND ADVERTISEMENTS - Maher Ahmed Ali Saleh (Indonesian EFL Journal, 2021)
This study intends to explore on protection available for Arabic language as compared with English in shops titles and advertisements in Aden province as being engulfed by the latter. The use of English as a Lingua Franca in communication has increased in the last decades in the field of advertising. The purpose of the current study is to enquire into consumers’ attitudes towards the use of English in advertisement and compare them with the views of those inclined towards the use of Arabic. However, some shop owners who are using English language in advertisements is due to many reasons which include; they tend to think that their costumers believe more on products from outside the country and thus they are sure when customers see foreign names it directly inclines to have more confidence towards the products. The study attempts to promote the use of Arabic language in Aden province towards customer satisfactions and beliefs in products named in their language. That means, not fighting against other languages as much as promoting the use of Arabic to go with all the challenges in the world. As a result, the customers trust using foreign language leads to Arabic language to become a dead like languages such as Latin or ancient Greek and hence the interest to using only Arabic language in names of the shops.Keywords: Protection of Arabic language; shop titles and advertisements.